2016
DOI: 10.1016/j.ijheatmasstransfer.2015.08.084
|View full text |Cite|
|
Sign up to set email alerts
|

Laser-Doppler measurements of the turbulent mixing of two rectangular water jets impinging on a stationary pool

Abstract: Turbulent mixing of parallel jet flows has broad engineering applications. For example, in Gen IV conceptual nuclear reactors, high-temperature flows mix in the lower plenum before entering the secondary cooling system. The mixing condition needs to be accurately estimated and fully understood. In addition, massive computational works involved in the design process necessitate high-fidelity experimental data sets for benchmarking simulation results. The purpose of this study is to use laser Doppler anemometry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 22 publications
2
9
0
1
Order By: Relevance
“…Based on this information, the Reynolds number of 9100 is defined based off the . This is consistent with the Reynolds number definition used by the experimental works [3,4,6]. The twin jets are separated (based on the centerline of each jet) with a spacing of 17.8 mm which results in a spacing ratio (S/a) of $3.07.…”
Section: Numerical Approachsupporting
confidence: 84%
See 2 more Smart Citations
“…Based on this information, the Reynolds number of 9100 is defined based off the . This is consistent with the Reynolds number definition used by the experimental works [3,4,6]. The twin jets are separated (based on the centerline of each jet) with a spacing of 17.8 mm which results in a spacing ratio (S/a) of $3.07.…”
Section: Numerical Approachsupporting
confidence: 84%
“…2 was made to be almost entirely transparent for additional experiments using noninvasive measurement techniques, such as laser Doppler velocimetry (LDV), particle image velocity (PIV), and laser-induced fluorescence. The TJWF was moved to Texas A&M University, where LDV and PIV data have been collected for CFD validation efforts [4][5][6][7] using the same boundary conditions as Crosskey and Ruggles. The LDV results of Wang et al includes streamwise velocity and vorticity profiles, Reynolds stress profiles, and merge/combined points.…”
Section: Experimental Test Facilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The nozzles exit Reynolds number was approximately 9100 and the turbulent intensity was 8%. Wang et al (2016) found that the longitudinal location of the merge point was between X = 1.72 and X = 3.45 and that of the combined point was X = 15.52. The turbulence study showed that the outer boundary of the combined jet and the outer edges of the two jets had higher turbulence levels due to high velocity gradients in those regions.…”
Section: Introductionmentioning
confidence: 95%
“…They found that the merge point location depends not only on the nozzles spacing but also on the nozzles exit condition such as the turbulent intensity. Recently, Wang et al (2016) experimentally studied two water jets flow issue from two parallel rectangular channels using two-component LDA technique. The nozzle spacing and the aspect ratio were respectively 3.1 and 15.…”
Section: Introductionmentioning
confidence: 99%